Anti-inflammatory activity of di-peptides derived from ovotransferrin by simulated peptide-cut in TNF-α-induced Caco-2 cells. (October 2017) - Wang, Xiong; Zhao, Yan; Yao, Yao; Xu, Mingsheng; Du, Huaying; Zhang, Mengya; Tu, Yonggang
Highlights: Sequences of OVT-derived di-peptides were obtained by stimulated peptide-cut. OVT-derived di-peptides were screened in Caco-2 cell inflammation model. CR, FL, HC, LL and MK derived from OVT exhibited anti-inflammatory effects. CR and HC inhibited the NF-κB and MAPK signaling pathway. LL, FL and MK inhibited the MAPK signaling pathway. Abstract: Proteins and bioactive peptides in avian egg whites exert anti-inflammatory activity. Here, we aimed to evaluate the anti-inflammatory effect of ovotransferrin (OVT) and its di-peptides by simulated peptide-cut using an in vitro model of TNF-α-induced inflammation in Caco-2 cells. Results showed that co-treatment with OVT can't inhibit the IL-8 secretion in TNF-α-induced Caco-2 cells. Among 18 di-peptides derived from OVT based on simulated peptide-cut, CR, FL, HC, LL and MK markedly decreased IL-8 secretion. Furthermore, these five di-peptides were able to significantly inhibited gene expression of pro-inflammatory cytokines, including TNF-α, IL-8, IL-6, IL-1β, and IL-12, and promoted gene expression of anti-inflammatory cytokines, such as IL-10, in Caco-2 cells. CR, FL, HC, LL and MK inhibited the phosphorylation of inhibitor of κB (IκB). Meanwhile, CR and HC decreased the phosphorylation of p-JNK and p-p-38. These results indicated that CR and HC inhibited the NF-κB and MAPK signaling pathway in TNF-α-induced Caco-2 cells. Nevertheless, LL, FL and MK exerted their anti-inflammatory activity via MAPK signaling pathway. The study suggested that CR, FL, HC, LL and MK have the potential to attenuate intestinal inflammation.